Incidence and outcome of peri-procedural cardiogenic shock: results from the international Euro Heart Survey PCI registry. Issue 2 (March 2020) - Weipert, Kay F; Bauer, Timm; Nef, Holger M; Hochadel, Matthias; Weidinger, Franz; Gitt, Anselm K; Zeymer, Uwe; Hamm, Christian W
Background: There is a large body of literature on acute myocardial infarction complicated by cardiogenic shock. However, very little is known about patients who are initially haemodynamically stable and develop cardiogenic shock during percutaneous coronary intervention. Methods: A total of 47, 407 consecutive patients were prospectively enrolled in the PCI Registry of the Euro Heart Survey Programme. We analysed interventions with peri-procedural complications that were classified as 'shock induced by procedure' on the case report form. Clinical and procedural characteristics as well as hospital outcomes of haemodynamically stable patients who developed cardiogenic shock during percutaneous coronary intervention were evaluated. Patients with haemodynamic instability at presentation prior to intervention were excluded. Results: A total of 68 patients (0.2%) developed cardiogenic shock as a complication of percutaneous coronary intervention. The majority of cases comprised acute coronary syndrome (60.3%) with complex lesions (93.1%). Most patients had multi-vessel disease (82.1%) and an ejection fraction less than 40% (58.1%). In the multivariate analysis, left main disease (odds ratio (OR) 9.51), ST-segment elevation myocardial infarction (OR 5.31) and multi-vessel disease without left main involvement (OR 3.32) were the strongest independent predictors of peri-procedural cardiogenic shock. Among these patients procedural success was low (66.1%) and in-hospital mortality was very high (39.7%). Conclusions: In this real-world registry the rate of haemodynamically stable patients who developed cardiogenic shock during percutaneous coronary intervention was very low. Patients at a priori high risk were more likely to be affected by this complication. The in-hospital mortality rate of these patients was very high.